1989
DOI: 10.1136/bmj.298.6680.1081
|View full text |Cite
|
Sign up to set email alerts
|

Risk behaviours for HIV infection among injecting drug users attending a drug dependency clinic.

Abstract: To study a range of possible risk factors for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…A national evaluation of schemes for exchanging needles found that seven per cent of clients had shared injecting equipment while in custody, but the number of clients who had been in prison was not known.4 A study of risk behaviours for HIV infection among injecting drug users attending a drug dependency unit in central London found that out of 32 who had been in prison in recent years eight had shared injecting equipment. 5 The Parole Release Scheme has estimated that every year 20 000 of the prisoners who have passed through the system have taken illicit drugs,6 but there have been no studies focusing specifically on risk behaviours for HIV infection among injecting drug users in prison. We therefore studied a group of injecting drug users in London, all of whom had been in prison since 1982, to determine the degree of illicit drug use in prisons, the prevalence of risk behaviours for HIV infection, and the uptake of available treatment with drugs within the prison system.…”
Section: Introductionmentioning
confidence: 99%
“…A national evaluation of schemes for exchanging needles found that seven per cent of clients had shared injecting equipment while in custody, but the number of clients who had been in prison was not known.4 A study of risk behaviours for HIV infection among injecting drug users attending a drug dependency unit in central London found that out of 32 who had been in prison in recent years eight had shared injecting equipment. 5 The Parole Release Scheme has estimated that every year 20 000 of the prisoners who have passed through the system have taken illicit drugs,6 but there have been no studies focusing specifically on risk behaviours for HIV infection among injecting drug users in prison. We therefore studied a group of injecting drug users in London, all of whom had been in prison since 1982, to determine the degree of illicit drug use in prisons, the prevalence of risk behaviours for HIV infection, and the uptake of available treatment with drugs within the prison system.…”
Section: Introductionmentioning
confidence: 99%
“…Lower syringe sharing rates (of around 9%) were found in a subsequent evaluation of syringe-exchanges in Wales [74]. Low and declining sharing rates were reported from a single site study of a major stand-alone London syringe-exchange [75], from six syringe-exchange and community recruited samples in London and South-West England [76], among drug dependence clinic attenders [16,77], general practice patients in Scotland [78,53,79], and among treatment and community recruited samples in London, Glasgow and Edinburgh [51,80,17]. Comparable studies in London, Glasgow and Edinburgh, using a six-month period for self report (as opposed to one month) found significant reductions from 1990 to 1991 in Glasgow and London in the percentage of injectors receiving used needles and syringes and a levelling from 1991 to 1992 [67,[81][82][83].…”
Section: Behavioural Change and Low And Stable Hiv Pre~alence Ratesmentioning
confidence: 99%
“…For example, in 1986, 63% of an Edinburgh agency sample reported sharing syringes at least once a week [12]. The published studies (mainly from Edinburgh and London) showed between 59% and 83% of injectors reporting sharing syringes (there were variations between studies in definitions, time periods, sampling and recall methods) [12,6,[13][14][15][16]. Confirmatory retrospective data for Edinburgh (collected in 1992) confirm this picture with 67% of injectors reporting sharing syringes during any year up to 1986 [17].…”
Section: The Situation In 1986 and 1987mentioning
confidence: 99%
“…In the U.K. only 118 cases of AIDS had been reported amongst intravenous drug users up to 31 December 1989, but 1,819 reports of HIV positive intravenous drug users had been received. A large proportion of these have been reported in Edinburgh where a substantial level of infection (at least 50% seropositive) has developed amongst the population of intravenous drug users (Robertson et al, 1986;Brettle et al, 1987;Hart et al, 1989). 8.7 The prevalence of HIV infection amongst intravenous drug users in some parts of the U.S.A. has lead to a serious public health problem (Weinberg & Murray, 1988).…”
Section: Blood Productsmentioning
confidence: 97%